Education Financing Management: Productivity and Efficiency of the Education System - Bambang Irawan; Maria Jashinta Elisabet Hamboer; Benget Tua Simarmata; Yulvitriyani Br Sebayang; Afif Alfiyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine education financing management based on the productivity and efficiency of the education system. This research is a literature review or literature review to formulate education financing management as the productivity and efficiency of the education system. The results of this study indicate that productivity measurement is an important management tool at all levels of the economy. Productivity measurement relates to changes in productivity so that efforts to increase productivity can be evaluated. Measurements can also be prospective and as input for strategic decision-making. The measure of productivity is different from efficiency. Efficiency is a measure of comparing the planned use of information with the actual use of inputs. If the real input is used, the greater the savings, the higher the efficiency level. Productivity is comparing output and input and prioritizing how to use both resources in producing goods or services. Efficiency is how to make the effect of a goal with a process that is 'cheaper'.